Evaluación de la melanosis del camarón blanco litopenaeus vannamei procesado en empacadora y sometido a congelación - Astudillo Morán, María José (2013)
An important factor to keep in mind during the whole technological process is the presence of melanosis consisting of a blackish appearance on the cuticle of the shrimp, which is a serious problem for producers, the high variability of absorption sulfite in the muscle causes the need for a fast and efficient process before freezing, as enzyme source phenomenon by the reaction of polyphenol oxidase (PPO) to oxidize compounds into quinines fenolíticos begins, usually immediately after the death of the animal, although in some cases has taken place in living specimens. In this investigation the following objective: To evaluate the concentrations of sodium metabisulfite in shrimp subjected to freezing processes versus presence of melanosis. The research was conducted in the baler EXORBAN SA located on Santa Rosa, province of El Oro Following this investigation concluded: The process of using sodium metabisulfite harvest begins in shrimp which are controls to verify the concentrations, then these controls remain in the receiving, sorting, packing and storage finely where it is found that the residual SO2 not to exceed the limits are 150 ppm. The sodium metabisulfite is currently the best choice for the development of control melanosis. In the microbiological analysis show no infections are below as indicated in the rules of hygiene. The statistical analysis presented significant difference in the three treatments.